Globalization and public administration: A complex relationship - Angelini , Elisabetta Croci (2011)
The article examines the relationship between globalization and public administration through economic theory principles and an example. Starting from the consideration of early concerns about globalization, it argues that although the size of government has rarely declined, its power has been eroded, making room on the one hand to the quest for global public goods, while on the other hand advocating for more local public goods and decentralization. University education, mainly publicly supplied in Italy as well as in many European countries, exemplifies the awkwardness of introducing best practices in a context of asymmetric information with many idiosyncratic features. - Reproduced.
Keywords: Globalization; Public administration